2010
DOI: 10.1063/1.3483761
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing-induced vertical phase separation of copper phthalocyanine: Fullerene bulk heterojunction in organic photovoltaic cells

Abstract: The effect of thermal annealing treatment on the morphology change in bulk heterojunction (BHJ) in organic photovoltaic cells was studied by photoemission spectroscopy. The results reveal that vertical phase separation upon annealing occurs in typical BHJ layer formed between planar molecule CuPc and spherical C60 with inhomogeneous concentration distribution in profile, varying from CuPc-rich near the air surface to C60-rich adjacent to the substrate interface. The morphology variation is associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…The central metal atom and substituents on the benzene rings of the phthalocyanine molecule influenced UV-vis absorbance; CuPcTs had strong absorption bands around 650 nm (Q bands) [63][64][65][66][67][70][71][72][73]. The characteristic maxima of CuPcTs were in the 300-800 nm range of the absorbance spectra, which was convenient for the analysis of the semitransparent thin PEI/CuPcTs/(PDADMAC/CuPcTs) n films.…”
Section: Film Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The central metal atom and substituents on the benzene rings of the phthalocyanine molecule influenced UV-vis absorbance; CuPcTs had strong absorption bands around 650 nm (Q bands) [63][64][65][66][67][70][71][72][73]. The characteristic maxima of CuPcTs were in the 300-800 nm range of the absorbance spectra, which was convenient for the analysis of the semitransparent thin PEI/CuPcTs/(PDADMAC/CuPcTs) n films.…”
Section: Film Fabricationmentioning
confidence: 99%
“…In fact, phthalocyanine molecules tend to aggregate in a kind of phase separation, e.g., if they are surrounded by a polymer matrix [29]. Under some conditions, phthalocyanine aggregation takes place in various complexes, including phthalocyanine-aggregated Pluronic nanoparticles, used in photodynamic therapy [88], and phthalocyanine-fullerene complexes, used to fabricate bulk heterojunctions for photovoltaic applications [63][64][65].…”
Section: Om Afm and Sem Characterizationmentioning
confidence: 99%
“…For various binary blends such as polymer:fullerene, polymer:polymer, or phthalocyanine:fullerene, surface segregation has recently been reported. [19][20][21][22][23][24] These studies suggested that the material with the lower surface energy is likely to be segregated into the air/fi lm interface while the material with higher surface energy is segregated to the fi lm/electrode interface, indicating that the vertical phase separation is strongly dependent on the surface energy of each material. For ternary blend fi lms, in which a third material is added to binary blends, the location of the third component has been studied for various materials such as conductive carbon black particles, [ 25 ] carbon nanotubes, [26][27][28] CaCO 3 nanoparticles, [ 29 ] and polymers.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4][5] Various attempts have been devoted to control the nanostructure of the mixed layer in SM bulk heterojunction (BHJ) OPVs. In CuPc:C 60 systems, controlled growth such as through alternative thermal deposition was successful in controlling the nanostructure and improving the interpenetrating networks.…”
Section: Introductionmentioning
confidence: 99%